APPLICATION OF UPPSALA THEORY IN THE INTERNATIONALIZATION OF FURNITURE PRODUCTS - Martin; Sudarmiatin Sudarmiatin; Imam Mukhlis (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
The research problem raised aims to find out how the process of internationalization of furniture companies is related to the Uppsala theory. This research is a case study with an object, namely the company Aida Furniture which is one of the Micro, Small and Medium Enterprises (MSMEs) engaged in the furniture industry. This research was conducted through a descriptive and qualitative approach. To obtain the necessary data, the authors conducted in-depth interviews with business owners from Aida Furniture. Determination of the subject is done purposively where the researcher determines the sampling by determining the special characteristics that are by the research objectives so that they are expected to be able to answer research problems. The biggest problem in the process of market internationalization is on the supply side where the government and universities are expected to be able to fill this gap by standardizing treatment in usage and other processes. In the internationalization process described, Uppsala's theory cannot be used to explain the internationalization process model at Aida Furniture. Meanwhile, the process of spreading sales areas can be explained by the Uppsala theory.